Keamanan Manusia Dalam Rencana Aksi Daerah: Implementasi Tujuan Pembangunan Berkelanjutan (Sustainable Development Goals) di Provinsi Nusa Tenggara Barat - Khairur Rizki; Muhammad Sood; Valencia Husni (Papua Journal of Diplomacy and International Relations, 2022)
The United Nations (UN) adopted the Sustainable Development Goals (SDGs) in 2015 to eliminate poverty, bring prosperity, and save the planet by 2030. As a UN member, Indonesia is also responsible for achieving SDGs. Indonesia’s commitment is shown by appointing the National Development Planning Agency (BAPPENAS) as the central coordinator and presenting a Presidential Regulation (Perpres) to encourage every region to be involved in implementing the SDGs. Accordingly, the Government of Nusa Tenggara Barat (NTB) issued the Regional Action Plan (RAD) as a reference for pursuing sustainable development in NTB. This study seeks to reflect on SDGs’ implementation in the NTB Regional Action Plan using the human security approach. This approach explains that providing a sense of security for humans is the ideal condition, including sustainable development. This study employs qualitative descriptive research in order to analyze NTB’s RAD from 2019 to 2023. The findings of this research reflect the suitability of the NTB Provincial Action Plan with the application of the human security concept in its implementation. KEYWORDSHuman Security; Nusa Tenggara Barat; Regional Action Plan; Sustainable Development Goals